THE POLITICAL SCIENCE IN THE REPUBLIC OF MACEDONIA: CHALLENGES AND PERSPECTIVES - Apostolovska stepanoska, Milena (International Academic Institute, 2019)
Тhe countries of Southeast Europe, following the collapse of the Berlin Wall, have faced radical socio-political changes. The political system based on power-sharing, human rights, individualism, freedom of speech, market economy were new concepts for the citizens in these countries. Direct political speeches, demonstrations, pamphlets, free interviews, analytical articles and free communication between the government and the citizens were something new in the political setting. Apart from living these political changes, the Republic of Macedonia, at the same time, separated from the Yugoslav Federation and gained the status of an independent state. In this manner it is important to be said that in that time the social - humanistic science was fully focused on social transition that was taking place. In these circumstances, in 1993/1994, the first political studies at the Faculty of Law at the University "Cyril and Methodius" were formed. This university is the largest and the oldest in the Republic of Macedonia. Since the establishment of the political science studies in the Republic of Macedonia, they were expected to give meaningful and practical implications and contribute to socially critical thinking and social reforms. There was an urgent need for improved understanding of certain social events. This urgency was reflected in the theoretical frame of certain social and political phenomena and their empirical monitoring. Тhe main topics that become dominant on the classes were the basic ethical, political and economic pillars on which capitalism and Western democracy relies. At the same time dramatically rejection of certain theories that were previously dominant over the years happened and this can be seen after the analysis of the curricula of these studies. The main aim of this research is to prove that the science in transition societies of the Southeastern Europe, including in the Republic of Macedonia was reflected by the development of the political environment in the society. This reflection is evident in the pronounced influence of the theory on account of empiricism, limited resources for empirical research, great and non-critical favoritism of Western theoretical thought, especially in the part of public politics.
Keywords: Transitional societies, Political science, Institutionalization